2013
DOI: 10.1021/ol4019419
|View full text |Cite
|
Sign up to set email alerts
|

Direct Transformation of Amides into α-Amino Phosphonates via a Reductive Phosphination Process

Abstract: The first general method for the reductive phosphination of amides in one pot has been developed. The reactions described provide a novel access to α-amino phosphonates in good to excellent yields, cover a broad scope of substrates such as secondary and tertiary amides, and do not require a low temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 49 publications
0
40
0
Order By: Relevance
“…Our previous studies revealed that 4 was more electrophilic than an ordinary N-alkyliminium ion 6, and reacted with mild nucleophiles. [15,16] Combining both of these unique properties, our method became high yielding and compatible with a number of sensitive functional groups.…”
Section: Dedicated To Professor Larry E Overman On the Occasion Of Hmentioning
confidence: 98%
“…Our previous studies revealed that 4 was more electrophilic than an ordinary N-alkyliminium ion 6, and reacted with mild nucleophiles. [15,16] Combining both of these unique properties, our method became high yielding and compatible with a number of sensitive functional groups.…”
Section: Dedicated To Professor Larry E Overman On the Occasion Of Hmentioning
confidence: 98%
“…An interesting approach to α-aminophosphonate synthesis, based on in situ reduction of amides with bis(cyclopentadienyl)zirconium hydrogen chloride (Cp 2 ZrHCl, the Schwartz's reagent) in the presence of dialkyl H-phosphonates, is presented in Scheme 3 [45]. The main advantages of this direct transformation of amides into aminophosphonates are a broad scope of substrates, mild reaction conditions, and good yields.…”
Section: Synthesis Of α-Aminophosphonates and Related Compoundsmentioning
confidence: 99%
“…With the growing interest in organocatalysis, new protocols were developed for enantioselective transformations of imines and related compounds into α-aminophosphonates. These transformations used quinine-squaramide [48] or chiral Brønsted acids [45] as catalysts [49,50].…”
Section: Synthesis Of α-Aminophosphonates and Related Compoundsmentioning
confidence: 99%
“…5a,7 The biological importance of this class of compounds continues to drive efforts toward their efficient and rapid synthesis (Scheme 1). [8][9][10][11][12][13][14] α-Amino phosphonic acids are generally prepared through formation of C−P bonds, for example, by the Pudovik reaction (Scheme 1; pathway a) or the Kabachnik-Fields reaction (pathway b). The Pudovik reaction involves the hydrophosphonylation of an imine 8 or an amide, 9 whereas, the Kabachnik-Fields reaction is a three-component reaction of an amine, an aldehyde, and a dialkyl phosphite.…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13][14] α-Amino phosphonic acids are generally prepared through formation of C−P bonds, for example, by the Pudovik reaction (Scheme 1; pathway a) or the Kabachnik-Fields reaction (pathway b). The Pudovik reaction involves the hydrophosphonylation of an imine 8 or an amide, 9 whereas, the Kabachnik-Fields reaction is a three-component reaction of an amine, an aldehyde, and a dialkyl phosphite. 10 Alternatively, α-amino phosphonic acids can be prepared through C−C bond formation, either through the addition of an anionic phosphonic analogue of glycine to an electrophilic carbon atom (pathway c) or through the addition of a nucleophile to a cationic phosphoglycine equivalent (pathway d).…”
mentioning
confidence: 99%